2018
DOI: 10.21037/jtd.2018.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-toxicity in childhood cancer survivors “Cure is not enough”

Abstract: Background According to the latest publication of data by the German Children's cancer registry (DKKR), the 5-year survival rate for children aged under 15 years is estimated with 85%. Since 1980, 47,650 patients have been documented (1). Attention is drawn towards cardiac or cardiovascular sequelae in childhood cancer survivors. Accordingly, this topic was covered in adult cancer survivor studies leading to the ESC position paper on cardiac toxicity, quoted in the subtitle mentioned above (2). There are publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…To highlight these underlying mechanisms, it would have been interesting to consider the important markers of cardiotoxicity, such as BNP and NT-proBNP markers,48,49 in addition to the echocardiograph assessment 50. This is an important topic because it has been reported that survivors have a considerably increased risk for premature cardiovascular diseases such as congestive heart failure 51,52. Protection strategies must continue to be prescribed, whereas exercise training should be implemented in pediatric oncology to slow survivors’ cardiotoxicity 53,54.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To highlight these underlying mechanisms, it would have been interesting to consider the important markers of cardiotoxicity, such as BNP and NT-proBNP markers,48,49 in addition to the echocardiograph assessment 50. This is an important topic because it has been reported that survivors have a considerably increased risk for premature cardiovascular diseases such as congestive heart failure 51,52. Protection strategies must continue to be prescribed, whereas exercise training should be implemented in pediatric oncology to slow survivors’ cardiotoxicity 53,54.…”
Section: Discussionmentioning
confidence: 99%
“…50 This is an important topic because it has been reported that survivors have a considerably increased risk for premature cardiovascular diseases such as congestive heart failure. 51,52 Protection strategies must continue to be prescribed, whereas exercise training should be implemented in pediatric oncology to slow survivors' cardiotoxicity. 53,54 It has been reported that a good cardiorespiratory fitness level is associated with cardiac health in childhood ALL survivors.…”
Section: Discussionmentioning
confidence: 99%
“… 48 However up to 57% of pediatric patients have asymptomatic ventricular dysfunction. 49 Risk factors for cardiotoxicity include use of anthracyclines at a young age (<4 years), high cumulative dose for age (≥200 mg/m 2 for age <1 year and ≥300 mg/m 2 for >1 year old), concurrent use of radiation therapy, and female gender. 48 , 49 Cardiotoxicity manifests as left or right ventricular systolic or diastolic dysfunction.…”
Section: Pulmonary Hypertension Associated With Cancer Therapymentioning
confidence: 99%
“… 49 Risk factors for cardiotoxicity include use of anthracyclines at a young age (<4 years), high cumulative dose for age (≥200 mg/m 2 for age <1 year and ≥300 mg/m 2 for >1 year old), concurrent use of radiation therapy, and female gender. 48 , 49 Cardiotoxicity manifests as left or right ventricular systolic or diastolic dysfunction. 50 Because of the risk of cardiotoxicity, echocardiography is obtained frequently with treatment and every 5 years after low dose anthracycline ± radiation therapy (<15 gray) exposure and every 2 years with high dose (>250 mg/m 2 ) or whenever a higher dose (>15 gray) of radiation therapy is used.…”
Section: Pulmonary Hypertension Associated With Cancer Therapymentioning
confidence: 99%
“…Research has shown that compared to normal individuals, childhood cancer survivors have a 5-15 fold increased risk of congestive heart failure, and once diagnosed, the 5-year survival rate is less than 50% [10] . Tumor combined with cardiovascular disease or cardiovascular complications induced by anticancer treatment have become the main cause of incidence rate and mortality/non cancerous death of child cancer survivors [11][12][13][14] . Therefore, early identi cation of high-risk children, successful screening and early treatment of children with cardiac damage are of great signi cance.…”
Section: Introductionmentioning
confidence: 99%